Permeability Characteristic and Failure Behavior of Filled Cracked Rock in the Triaxial Seepage Experiment - Xinyu Liu; Zhende Zhu; Aihua Liu (Advances in Civil Engineering)
Filling is commonly found in natural cracked rock mass. As the weakest part of the rock, the filling properties directly affect the rock deformation and strength, permeability, and so on and affect the safety and stability of the rock mass engineering. In this study, a single slit has been preset in sandstones and filled with different physical properties materials. Based on the laboratory triaxial seepage test, the permeability and strength characteristics of filled cracked sandstones are analyzed, and the failure modes are obtained. The main findings of this study are as follows: (1) The permeability coefficient peak value of the filled cracked rock appears before the stress peak. (2) At the same confining pressure growth rate, the peak stress growth rate of the filled cracked rock is generally higher than that of the intact rock and the strength growth rate of the cracked rock increases with the length of the fracture. The strength characteristics of the filling in the uniaxial compression tests and triaxial seepage tests are significantly affected by the hydraulic properties. (3) The strength and permeability coefficients of cracked rock filled with cement mortar are more sensitive to the change of confining pressure, while under the same condition, the ones of cracked rock filled with gypsum mortar are stable. (4) According to the failure mechanism, under the seepage stress, the secondary cracks can be divided into 3 types and the failure modes can be divided into 2 types.